Penggunaan "Uang Haram" Untuk Ibadah Haji - Idwal B (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
The jurists have different opinion regarding the use of illicit money for hajj purpose. In this case, their opinion are divided into two groups: First, imam Ahmad ibn Hanbal and his followers (hereinafter referred to as Hanabilah) found pilgrimage with illicit money is not legitimate. Thus, those who carry it out are not rewarded, even sinful. Second, imam Muhammad ibn Idris al-Shafi’i, Malik ibn Anas and Abu Hanifa, and many previous scholars (hereinafter referred to as jumhur jurists) which states that the pilgrimage with illicit money is valid, but illicit, or in the words of Abu Hanifah named as makruh tahrim, Although his obligation to perform hajj is considered as legitimate, but he sinned. Hajj is not haram, but the use of money earned by unclean way is a sinful. Because something that must be attributed with the law may not haram. People who are on pilgrimage is already deemed to have been (rightfully) although his Hajj pilgrimage is not accepted and not rewarding. Although formal legal arguments of the jurists jumhur more powerful, but to anticipate the danger (harm) and the slander that would arise, namely the habit of doing that is haram for something that is halal, which would have a negative impact on themselves, family, and the community at large, then Hanabilah opinion that considers unauthorized person hajj pilgrimage with unclean person is very appropriate and suitable to be applied in the present society. This is useful in order not to get people motivated to do evil / unclean deeds for the sake of the holy Hajj